La literaturización de la experiencia del exilio como síntesis de la trayectoria política barojiana - Crippa, Francesca (Verba hispanica, 2015)
In his short novel titled Susana y los cazadores de moscas (1938), Baroja tells the story of an ordinary person who finds himself compelled to live in another country because of the Civil War. Baroja partially identifies himself in his main character, whose name is Miguel Salazar, because he himself had to build a new life in Paris, where he decided to go after the war broke out. The aim of this work is to analyze the novel according to the ideological and biographical correspondences between the author and the main character in order to confirm the possibility of an autobiographical interpretation for one of the less known novels written by the Basque writer.
Keywords: Baroja, Pío, 1872-1956; Spanish literature; španska književnost; generacija 98; državljanska vojna; izgnanstvo; kratka proza